Taming the Unruly Public Policy Horse in Private International Law in Family Law: A Pragmatic Singaporean Approach to the Recognition of Foreign Same-Sex Marriages and Divorces. (21st June 2021) - Chan, Leon Vincent
Abstract: With the legalisation of same-sex marriages by more states, it is a matter of time before jurisdictions that have yet to do so will need to decide on the recognition of foreign same-sex marriages and divorces. Public policy – the unruly horse – peers its head out again even if these marriages and divorces pass the muster of the common law private international law rules. This article explores the role of public policy in such situations and proposes a framework for the balancing of the claimed rights, comity, and public policy. Applying the proposed framework, even if there is a public policy against same-sex marriage, this public policy should play a diminished role in private international law such that foreign same-sex marriages and divorces can be recognised by the forum.